Pencegahan Penyalahgunaan Narkoba Guna Mewujudkan Sidorejo Sebagai Desa Bersinar - Paradik, Patrick Servanda Grotius; Pratiwi, Isabela Dwi; Nugraha, Rangga; Anwari, Muhammad; Dinata, Rico Arta; Silvian, Mega Bela; Naimah, Naimah; Handayani, Nurma (Abdi Panca Marga, 2022)
Sidorejo Village is one of the developed villages in the Rowokangkung sub-district, Lumajang Regency. Sidorejo Village has very minimal drug abuse problems. However, the community and the government of Sidorejo Village are very enthusiastic about preventing drug abuse. This makes the people of Sidorejo aware of the dangers of drugs. This journal aims to realize Sidorejo Village, Rowokangkung District, Lumajang Regency as a Shining Village. The form of Shining village innovation in preventing the dangers of drug abuse is intended to have an impact on regional conduciveness. The methods used to realize the Shine village include conducting counseling and campaigns. The counseling carried out in the village of Sidorejo was counseling entitled "Prevention of Drug Abuse" Making Sidorejo the village of Shining in addition to counseling, a campaign was also carried out in the form of an resistant to drug pledge. The results obtained are that the prevention of drug abuse in Sidorejo village, Rowokangkung district, Lumajang district has been implemented according to the wishes of the community to realize the Shining village is very adequate. This is what prompted Sidorejo to become a Shining village. Keywords: shine, pledge, village, drugs, BNN.